Preparation method of polyurethane-liquid metal composite elastic heat material
By combining liquid metal metal with polyurethane materials, the liquid metal-polyurethane composite material with high thermal conductivity performance is prepared to solve the problem of high stress on shape memory alloy alpine thermal materials at this stage. Cost and body type.
Patent Information
- Application Number
- CN202411646960.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-18
AI Technical Summary
At this stage, the shape memory alloy elastic thermal materials need high stress to generate huge adiabatic temperature change under uniaxial stress, resulting in huge size and high cost of refrigeration equipment, insufficient material brittleness and fatigue life, low refrigeration efficiency, and limited temperature zone. .
By combining liquid metal metal with polyurethane materials, the liquid metal-polyurethane composite material with high thermal conductivity is prepared, using the good thermal conductivity and liquidity of liquid metal to improve the thermal conductivity of polyurethane, and the liquid metal is uniformly dispersed through ultrasonic oscillation and other methods to uniformly dispersed the liquid metal. , Reduce driving stress.
The high thermal conductivity, the prominent thermal effects, the extremely low driving stress, and the simple preparation method are achieved, reducing the design cost and body shape of the refrigeration equipment, and improving the working life of the refrigeration efficiency and the working life of the material.
Smart Images

Figure CN119350837A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solid-state refrigeration, and in particular to a method for preparing a high molecular polymer solid-state refrigeration material. Background Art
[0002] Refrigeration technology is widely used in various fields. At present, the most commonly used refrigeration method is vapor compression refrigeration. However, hydrofluorocarbons used in vapor compression refrigeration can cause serious harm to the climate, such as global warming. Therefore, the development of new zero-emission, pollution-free green refrigeration technology has received widespread attention. In recent years, solid-state refrigeration technology based on the thermal effect of solid materials driven by an external field has become an alternative to traditional refrigeration technology due to its high efficiency and environmental protection.
[0003] Elastic caloric refrigeration technology is currently the most widely studied solid-state refrigeration technology. Its principle is based on the elastocaloric effect of the material, that is, the elastocaloric material produces a structural phase change inside under the action of uniaxial stress, which in turn produces a heat absorption / release effect. Among them, shape memory alloys have been widely studied as typical elastocaloric materials. For example, NiMnTi shape memory alloys and NiTi shape memory alloys can produce adiabatic temperature changes ΔT of about 31.5°C and 38.5°C under uniaxial stress. However, in order to obtain a huge ΔT, the current elastocaloric alloy materials require a stress of hundreds of megapascals to drive the alloy to undergo a structural phase change. The high stress causes the refrigeration equipment to require a huge motor to drive the alloy to produce an elastocaloric effect, which greatly increases the design cost of the refrigeration equipment. Secondly, the brittleness of most alloys also seriously affects their fatigue life, making it difficult to meet the working life requirements required for refrigeration. In addition, the elastocaloric effect occurs near the phase transition temperature of the shape memory alloy, and the phase transition temperature range of the alloy is usually within 10°C. The farther the working temperature is from the phase transition temperature, the more the required driving stress will increase sharply, and the cooling efficiency will decrease sharply, which means that the elastocaloric cooling temperature range can only be limited to a relatively narrow temperature range. Therefore, the above problems of shape memory alloy elastocaloric materials at this stage hinder the further commercialization of elastocaloric cooling technology.
[0004] In recent years, people have found that shape memory polymers also have similar elastocaloric effects as shape memory alloys, and they have the advantages of simple preparation and low driving stress. Among them, polyurethane, as a typical type of shape memory polymer material, has received widespread attention. However, due to the low thermal conductivity of polyurethane (0.5 ~ 1 W / m ℃), heat cannot be quickly and timely transferred to the external environment during uniaxial stress driving, resulting in a large loss of its energy, limiting the further improvement of the elastocaloric effect of polyurethane. The traditional method of adding thermally conductive solid particles to polyurethane to improve thermal conductivity often has a cumbersome preparation process, and the thermally conductive particles are easy to agglomerate, causing uneven composition inside the polymer. Therefore, it is necessary to develop a material with high thermal conductivity, large elastocaloric effect, low driving stress, and simple preparation method to meet the actual needs of elastocaloric refrigeration technology. Summary of the invention
[0005] The invention provides a method for preparing a polyurethane material with high thermal conductivity. The polyurethane prepared by the method has good thermal conductivity, outstanding elastic-caloric effect, extremely low driving stress and a simple preparation method.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] A method for preparing a polyurethane-liquid metal with high thermal conductivity, comprising:
[0008] Step S1, selecting a liquid metal material A and a polyurethane material B with a suitable melting point and a dissolving liquid C of the material B;
[0009] Step S2, adding polyurethane material B into dissolving solution C and stirring until completely dissolved, to prepare a solution of material B;
[0010] Step S3, adding a certain mass of material A to the solution of material B, stirring and ultrasonically oscillating the solution, so that material A is evenly dispersed in the solution, to obtain a mixed solution of material A and material B;
[0011] Step S4, pouring the mixed solution obtained in step S3 evenly into the mold;
[0012] Step S5, placing the mold containing the mixed solution into a drying oven, drying and molding at high temperature, and finally obtaining a high thermal conductivity liquid metal-polyurethane composite elastic thermal material D composed of material A and material B.
[0013] Optionally, the material A may be one of GaIn and GaInSn alloys with a low melting point, and the melting point thereof is below 20° C. The material B may be selected from different types of polyurethane polymers.
[0014] Optionally, the material B polyurethane refers to a type of polymer material containing a urethane characteristic unit in the main chain, which is a polymer compound generated by the reaction of a diisocyanate or a polyisocyanate with a compound having more than two hydroxyl groups, and its chemical formula is: (C 10 H 8 N 2 O.C 6 H 14 O 3 )n.
[0015] Optionally, in step S1, the dissolving liquid C may be a tetrahydrofuran solution or a dimethylformamide solution with a purity of more than 99.5%.
[0016] Optionally, in step S2, the polyurethane material B is added to the dissolving liquid C at a ratio of xg / 100ml, wherein the value of x is 3 to 20.
[0017] Optionally, in step S3, the mass fraction of material A in the composite material D is y wt.%, wherein the value of y is 3 to 20.
[0018] Optionally, in step S3, the stirring method may be mechanical stirring or magnetic stirring, and the stirring time may be 30 to 60 minutes.
[0019] Optionally, in step S5, the drying temperature may be between 50 and 80° C., and the drying time may be between 4 and 8 hours.
[0020] Furthermore, the present invention also provides the application of the high thermal conductivity liquid metal-polyurethane composite material D in elastic-caloric refrigeration.
[0021] The advantages of the technical solution provided by the present invention include:
[0022] Liquid metal has good fluidity and is evenly distributed when mixed into polyurethane, solving the problem of easy agglomeration of traditional thermal conductive solid particles;
[0023] The incorporated liquid metal improves the thermal conductivity of polyurethane;
[0024] Liquid metal-polyurethane materials with higher thermal conductivity have larger adiabatic temperature change in the elasto-caloric effect;
[0025] The driving stress required for liquid metal-polyurethane materials to produce the elastocaloric effect is greatly reduced, far lower than the driving stress required for shape memory alloys, which greatly reduces the requirements and costs of elastocaloric cooling technology equipment and has good commercial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0027] Figure 1 This is a flow chart of the preparation of the polyurethane-liquid metal composite material according to Example 1 of the present invention;
[0028] Figure 2 These are appearance diagrams of the polyurethane-12 wt.% liquid metal composite material of Example 1 of the present invention in (a) flat, (b) bent, and (c) stretched states;
[0029] Figure 3 The electron microscope microscopic morphology of the polyurethane-liquid metal composite material of Example 1 of the present invention, wherein (a) and (b) are surface morphology of pure polyurethane and polyurethane-12 wt.% liquid metal composite materials, respectively, and (c) and (d) are cross-sectional morphology of pure polyurethane and polyurethane-12 wt.% liquid metal composite materials;
[0030] Figure 4 (a) is a cross-sectional view of the polyurethane-12 wt.% liquid metal composite material of Example 1 of the present invention under an electron microscope. In the figure, the four regions P1, P2, P3, and P4 are liquid metals flowing out of the material. These four regions are selected for energy spectrum analysis of elemental composition. The results of the energy spectrum analysis of the four regions are shown in FIG. Figure 4 (b)
[0031] Figure 5 This is a graph showing the relationship between the thermal conductivity of the polyurethane-liquid metal composite material and the liquid metal content in Example 2 of the present invention;
[0032] Figure 6 is the temperature change during the measurement of the elasto-caloric effect of the pure polyurethane and the polyurethane-liquid metal composite material in Example 2, wherein (a) is the temperature change value of the pure polyurethane material and the polyurethane-12 wt.% liquid metal composite material when the uniaxial stress is stretched to 3 times the elongation, wherein the stress loading rate is 0.41 s -1 (b) Temperature change of pure polyurethane material and polyurethane-12 wt.% liquid metal composite material during the process of completely unloading stress from 3 times the stretching length to the initial state, where the stress unloading rate is 0.41 s -1 ;
[0033] Figure 7This is a stress-strain relationship diagram of the polyurethane-12 wt.% liquid metal composite material in Example 2 of the present invention when performing elastic-caloric measurement. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the present invention more clear, the technical solution of the present invention will be described in detail below with reference to the accompanying drawings and specific embodiments.
[0035] Example 1
[0036] In this embodiment, there is a low melting point liquid metal Ga 64.6 In 20.3 Sn 15 And strength grade 85A thermoplastic polyurethane elastomer raw material.
[0037] The preparation method of the polyurethane-liquid metal composite elastic thermal material prepared from the above two materials is as follows Figure 1 As shown, taking the mass percentage of liquid metal as 12 wt.% as an example:
[0038] (1) Add 5 g of polyurethane raw material into 100 ml of tetrahydrofuran (tetrahydrofuran of chemical purity), and stir the solution continuously until the polyurethane raw material is completely dissolved;
[0039] (2) Weigh 3.636 g of liquid metal Ga 64.6 In 20.3 Sn 15 alloy and add it to the solution prepared in the previous step;
[0040] (3) subjecting the solution obtained in step (2) to mechanical stirring and ultrasonic oscillation for about 1 h to uniformly disperse the liquid metal alloy in the solution;
[0041] (4) pouring the solution in the step into a mold made of polytetrafluoroethylene;
[0042] (5) The polyurethane-liquid metal composite material is demolded and taken out of the mold by heating at 60° C. in a drying oven for 4 hours to completely evaporate the solvent.
[0043] The composite materials with different liquid metal contents only need to adjust the mass of the liquid metal in step 2, wherein the pure polyurethane material does not contain any liquid metal material.
[0044] Figure 2 Shown are the appearances of the obtained polyurethane-12 wt.% liquid metal composite material in flat, bent and stretched states. Figure 3 The microscopic morphology of the material taken with a scanning electron microscope is shown. Figure 3(a) (b) show the surface morphology of pure polyurethane and polyurethane-12 wt.% liquid metal composite. The results show that the pores on the surface of polyurethane-12 wt.% liquid metal composite are significantly reduced. Figure 3 (c) and (d) show the microscopic morphology of the cross-sections of the two samples. The results show that the molecular chain morphology of the polyurethane-12 wt.% liquid metal material changes, the width increases, and the gaps between the chains are filled with liquid metal droplets. Figure 4 (a) is a cross-sectional view of polyurethane taken by a scanning electron microscope. The four regions P1, P2, P3, and P4 in the figure are droplets of liquid metal. The composition of the droplets is determined using the energy spectrum function of the scanning electron microscope, as shown in Figure 1. Figure 4 (b) The energy spectrum results show that the elemental composition of the four regions is relatively consistent, and the composition of the metal droplet is determined to be Ga 64.6 In 20.3 Sn 15 .
[0045] Example 2
[0046] In this embodiment, there are pure polyurethane materials and polyurethane-liquid metal composite materials, wherein the mass proportion of liquid metal in the polyurethane-liquid metal composite materials is 4 wt.%, 8 wt.%, and 12 wt.%, respectively.
[0047] The thermal conductivity of the above four materials was measured using a NETZSCH LFA 467 laser thermal conductivity tester. The results are as follows: Figure 5 The measurement results show that the thermal conductivity of the material increases with the increase of liquid metal content.
[0048] The elasto-caloric effect of pure polyurethane material and polyurethane-12 wt.% liquid metal material was measured by a test platform consisting of an infrared camera and a tensile testing machine. The temperature change of the sample was recorded by an infrared thermal imager (T890-2 ECO, TestoSE & Co. KGaA) with a recording frequency of 0.9 s. -1 , and the infrared emissivity is 0.91. The tensile test was carried out using the LD23.305 universal testing machine of Shanghai Lishi Co., Ltd. The measurement sample was cut from the sample prepared in Example 1, and the size was about 40×20×0.02 mm. Figure 6 (a) shows the results of polyurethane and polyurethane-12 wt.% liquid metal materials at 0.41 s -1 Under the loading stress rate, the maximum surface temperature change when the sample elongation is 3, Figure 6 (b) The two samples were stretched at 0.41 s from the elongation of 3. -1Maximum temperature change when unloading stress. The results show that the polyurethane-12wt.% liquid metal material can achieve a positive temperature change of about 8.7℃ when loading and a negative temperature change of about -5.5℃ when unloading, while the pure polyurethane material only has a temperature change of about 6.8℃ and -4.5℃ during loading and unloading. This shows that the polyurethane-12 wt.% liquid metal material has a better elastic-caloric effect.
[0049] Figure 7 Shown in Figure 6 During the measurement of the elastic-caloric effect, the stress-strain curve of the polyurethane-12 wt.% liquid metal material during loading and unloading showed that the material has good flexibility and only requires a stress of about 5 MPa when the elongation reaches 3. This shows that the material only needs a very small stress to achieve a large elastic-caloric effect.
[0050] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a polyurethane-liquid metal composite elastocaloric material, characterized in that: include: Step S1, selecting a liquid metal material A and a shape memory polymer material B with a suitable melting point and a dissolving liquid C of the material B; Step S2, adding polyurethane material B into dissolving solution C and stirring until completely dissolved, to prepare a solution of material B; Step S3, adding a certain mass of material A to the solution of material B, stirring and ultrasonically oscillating the solution, so that material A is evenly dispersed in the solution, to obtain a mixed solution of material A and material B; Step S4, pouring the mixed solution obtained in step S3 evenly into the mold; Step S5, placing the mold containing the mixed solution into a drying oven, drying and molding at high temperature, and finally obtaining a high thermal conductivity liquid metal-polyurethane composite thermal elastic material D composed of material A and material B; Material A is selected from one of GaIn and GaInSn alloys with a low melting point, and its melting point temperature is below 20° C. Material B is selected from different types of polyurethane polymers.
2. The method according to claim 1, characterized in that Material B Polyurethane refers to a type of polymer material containing a characteristic unit of urethane in the main chain. It is a polymer compound generated by the reaction of diisocyanate or polyisocyanate with a compound having more than two hydroxyl groups. Its chemical formula is: (C 10 H8N2O·C6H 14 O3)n.
3. The method according to claim 1, characterized in that In step S1, the dissolving liquid C can be selected from tetrahydrofuran solution and dimethylformamide solution, and the purity is above 99.5%.
4. The method according to claim 1, characterized in that: In step S2, the polyurethane material B is added to the dissolving liquid C at a ratio of xg / 100ml, wherein the value of x is 3 to 20.
5. The method according to claim 1, characterized in that In step S3, the mass fraction of material A in the composite material D is y wt.%, wherein the value of y is 3 to 20.
6. The method according to claim 1, characterized in that In step S3, the stirring method is mechanical stirring or magnetic stirring, and the stirring time is 30 to 60 minutes.
7. The method according to claim 1, characterized in that In step S5, the drying temperature of the composite material is 50 to 80° C., and the drying time is 4 to 8 hours.
8. The method according to claim 1, characterized in that Doping with liquid metal improves the thermal conductivity of polyurethane materials.
9. The method according to claim 1, characterized in that: The polyurethane-liquid metal composite material has obvious temperature changes when it is stretched under loading stress and returns to the initial state under unloading stress.
10. Application of the polyurethane-liquid metal composite elastocaloric material prepared by the method according to any one of claims 1 to 9 and the preparation method thereof in the field of refrigeration.
Citation Information
Patent Citations
Liquid metal composite material, preparation method, remodeling method and recycling method
CN112280284A
Preparation method of liquid metal-based composite flexible conductive material
CN117410030A
Biosafe heat dissipation film and preparation method thereof
CN117467273A
Ternary heat-conducting insulating composite material and preparation method thereof
CN117487117A
Method of synthesizing a thermally conductive and stretchable polymer composite
US20200362218A1